Global Financial Crisis in South Asia and its Impact on Pakistan’s SMEs Sector by Using CGE Model - Syed, Anwar Ali Shah G; Memon, Muhammad Aslam; Halepoto, Ali Hassan; Shaikh, Faiz M (Journal of Asian Business Strategy, 2012)
This research investigates the Global Financial Crisis in South Asia and its impact on SMEs sector in Pakistan by using GE model. The main objectives of this research are to provide detailed overview of Globalization economic crisis and SMEs sector by using the General Equilibrium Model. Data were collected from 400 SMEs by using cross sectional data from four provinces by using simple random techniques. The Global trade analysis Purdue (GTAP) model is used to analyze the possible impact of Globalization on Pakistan’s economy in single-country, single-sector applied General Equilibrium frame work. It was revealed that from last two year globalization and economic recession has negative impact on the SMEs sector in Pakistan. After employing the simplified static analysis framework based on simulations reveal that Globalization Economic recession have influenced negatively on the economy of Pakistan The general inflation rate is increased and living standard is decreased and purchasing power is also decreased it has negative impact of the growth of SMEs in Pakistan and ultimately the economy of Pakistan.